2004
DOI: 10.1182/blood-2003-06-1850
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 gene promoter polymorphisms influence the clinical outcome of diffuse large B-cell lymphoma

Abstract: The aim of the study was to investigate whether interleukin-10 (IL-10) genetic polymorphisms influence this cytokine production as well as the incidence and outcome of diffuse large B-cell lymphoma (DLBCL). The frequency of IL-10 -1082G allele was found to be higher in 199 patients with DLBCL as compared with 112 control subjects (0.47 versus 0.39, P ‫؍‬ .043). Increased serum levels of IL-10 were associated with adverse prognostic factors and poor DLBCL outcome. The frequencies of IL-10 -819T and IL-10 -592A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
118
2
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 38 publications
13
118
2
10
Order By: Relevance
“…In NHL, SNPs of several genes have been previously related to lymphoma susceptibility, such as genes coding for xenobiotic proteins (GSTT1, PON1, Methionine synthase), 26,27 inflammation regulator cytokines (IL1, IL10, TNFa), [28][29][30] mismatch repairing elements (hMSH2), 31 or oncoproteins (H-ras 1). 32 Since BCL6 plays a crucial role during both normal B-cell maturation and lymphomagenesis, it has been hypothesized that constitutional or acquired mutations of putative functional elements may impact on lymphoma predisposition or lymphoma outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In NHL, SNPs of several genes have been previously related to lymphoma susceptibility, such as genes coding for xenobiotic proteins (GSTT1, PON1, Methionine synthase), 26,27 inflammation regulator cytokines (IL1, IL10, TNFa), [28][29][30] mismatch repairing elements (hMSH2), 31 or oncoproteins (H-ras 1). 32 Since BCL6 plays a crucial role during both normal B-cell maturation and lymphomagenesis, it has been hypothesized that constitutional or acquired mutations of putative functional elements may impact on lymphoma predisposition or lymphoma outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Increased IL-10 plasma levels and poor outcome of some lymphoma entities have been shown, suggesting an role for IL-10 in lymphoma development. 3,4,9,22 Recently Lech-Maranda and co-workers reported that homozygocity for À1087A (rs1800896 A/G) of the IL-10 promoter is associated with lower rates of complete remission and lower overall survival (OS) in patients with diffuse large B-cell lymphoma (DLBCL), whereas Berglund and co-workers showed an absence of such an association. 22,23 In a recent epidemiological multicenter study, evidence was provided that for carriers of the IL-10 À3538A allele (rs1800890 A/T) the risk of NHL is doubled, but this was not verified by a follow-up study.…”
mentioning
confidence: 98%
“…26,27 In fact, increased serum levels of IL-10 in diffuse large B cell lymphoma was detected in 20% of NHL patients 26,28 and was correlated with poor prognosis including significantly shortened overall survival (OS) and disease-free survival (DFS). 26,29,30 It was shown that IL-10 is also produced by MDSCs.…”
Section: Introductionmentioning
confidence: 99%